PEMANFAATAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) UNTUK IDENTIFIKASI KANDUNGAN FORMALIN PADA CILOK DI KECAMATAN ROGOJAMPI: Use Of Red Dragon Skin (Hylocereus Polyrhizus) For Identification Of Formalin Content In Cilok In Rogojampi District - Abdur Rohman; Bagus Setyawan; Arfiati Ulfa Utami (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2023)
The use of formalin as a food preservative is still common today. One type of food that is mixed with formaldehyde preservatives is cilok. There is a simple way without using chemicals to detect the formaldehyde content in cilok, namely using red dragon fruit skin. Red dragon fruit skin is waste that is not utilized and has the potential to provide natural coloring to food. Anthocyanin is a type of compound that reacts easily when mixed with acid or base compounds. The anthocyanin content in dragon fruit skin can identify the presence of formalin compounds in food. Anthocyanin has the same strong acid properties as formalin so when anthocyanin meets formalin, the formalin content can be easily observed organoleptically. This study aims to determine the formalin content in cilok taken in Rogojampi District in as many as 19 samples using a cross-sectional study method. The test results showed that the samples tested were negative or did not contain formalin.